Abstract and Lexically Specific Information in Sound Patterns: Evidence from /r/-sandhi in Rhotic and Non-rhotic Varieties of English. (December 2015) - Cohen-Goldberg, Ariel M.
Phonological theories differ as to whether phonological knowledge is abstract (e.g., phonemic), concrete (e.g., exemplar-based), or some combination of the two. The abstractness/concreteness of phonological knowledge was examined by analyzing the process of /r/-sandhi in two corpora of spoken English. Two predictions of exemplar-based theories were examined: the extent to which a word manifests a particular sound pattern like /r/-deletion should be influenced by (1) its lexical frequency and (2) its distribution in the language with respect to the sound pattern's conditioning environment. Lexical frequency was found to influence /r/-sandhi in a corpus of rhotic American English but not in a corpus of predominantly non-rhotic British English. No effect of a word's long-term distribution was found in either corpus. These results support theories proposing that phonological knowledge is both word-specific and abstract and indicate that speakers do not store all phonetic detail that is in principle available to them. The factors that may favor the use of word-specific versus abstract representations are discussed.